Improving Eighth Graders' Writing Skills Using Guided Questions at SMP Negeri 20 Palu - Sari, Nupita; Manurung, Konder; Lebagi, Desrin; Rofiqoh, Rofiqoh (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to determine whether the guided question technique is effective in improving the writing skills of grade VIII students at SMP Negeri 20 Palu. The researcher used a quasi-experimental research design. The population of this study consisted of 111 class VIII students at SMP Negeri 20 Palu. The sample of this study consisted of class VIII B, an experimental class with 29 students, and class VIII C, a control class with 29 students. The sample selection in this study used simple random sampling. The researcher administered pretests and posttests during data collection. The results showed that the average value of the experimental class students on the posttest (75.29) was significantly higher than that of the control class students (58.62). The significance value (Asymp. 2-tailed) is 0.001, which is smaller than the p-value of 0.05; this indicates that the alternative hypothesis (Ha) is accepted. In conclusion, the guided question technique effectively improved the writing skills of grade VIII students at SMP Negeri 20 Palu.